212k views
2 votes
Solve |2x - 1| + 3 = 6.

2 Answers

7 votes

Steps to solve:

|2x - 1| + 3 = 6

~Subtract 3 to both sides

|2x - 1| = 3

~Since we are working with an absolute value, one answer will be positive and one will be negative.

2x - 1 = 3

~Add 1 to both sides

2x = 4

~Divide 2 to both sides

x = 2

2x - 1 = -3

~Add 1 to both sides

2x = -2

~Divide 2 to both sides

x = -1

Best of Luck!

User Yalitza
by
5.8k points
6 votes

Answer:

x =2 x = -1

Explanation:

|2x - 1| + 3 = 6.

Subtract 3 from each side

|2x - 1| + 3-3 = 6-3

|2x - 1|= 3

An absolute value has two solutions, one positive and one negative

2x-1 =3 2x -1 = -3

Add 1 to all sides

2x-1+1 =3+1 2x-1+1 = -3+1

2x = 4 2x =-2

Divide by 2

2x/2 = 4/2 2x/2 = -2/2

x =2 x = -1

User LeAthlon
by
4.8k points